1996
DOI: 10.1152/ajpgi.1996.271.4.g613
|View full text |Cite
|
Sign up to set email alerts
|

Histamine H2 receptor activates adenylate cyclase and PLC via separate GTP-dependent pathways

Abstract: Previously, we demonstrated that a single histamine H2 receptor can couple to both the adenosine 3',5'-cyclic monophosphate and inositol 1,4,5-trisphosphate/intracellular Ca2+ signaling pathways in a stimulatory manner. We undertook the present studies to fur her characterize the postreceptor events involved in H2 receptor dual signaling. Histamine H2 receptor-mediated signal transduction was examined in isolated cell membranes prepared from purified canine parietal cells and HEPA cells (rat hepatoma cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
18
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 0 publications
3
18
0
Order By: Relevance
“…This was confirmed in experiments with a cloned H 2 receptor in which the direct linkage of a single receptor to both adenylyl cyclase and PLC via separate GTP-dependent mechanisms was demonstrated (37,38). Several other reports also showed that a single type of receptor may be associated with more than one G protein and thus lead to multiple intracellular signaling systems, although the mechanism by which different factors may be involved in regulation of the plurality of receptor-mediated signaling remains unknown.…”
Section: Discussionmentioning
confidence: 72%
“…This was confirmed in experiments with a cloned H 2 receptor in which the direct linkage of a single receptor to both adenylyl cyclase and PLC via separate GTP-dependent mechanisms was demonstrated (37,38). Several other reports also showed that a single type of receptor may be associated with more than one G protein and thus lead to multiple intracellular signaling systems, although the mechanism by which different factors may be involved in regulation of the plurality of receptor-mediated signaling remains unknown.…”
Section: Discussionmentioning
confidence: 72%
“…Histamine mediated activation of its receptor leads to signaling through both adenylate cyclase (AC) and phosphoinositide (PI)/protein kinase C (PKC) second messenger systems (2,5). This observation has been made in both primary systems such as the parietal cell (6 -8) as well as in transfected cell models (9,10). The importance of this receptor in regulating multiple physiological events lends relevance to elucidating the pathways involved in post-receptor signaling.…”
mentioning
confidence: 94%
“…Interestingly, antihistamine drugs were neuroprotective only when both H 1 and H 2 histamine receptors were blocked. H 2 receptors are linked to both adenylate cyclase and phospholipase C in pathways that lead to calcium mobilization (27)(28)(29). The phospholipase C pathway is also used by H 1 receptors.…”
mentioning
confidence: 99%